Factors affecting performance of family-owned small and medium-sized enterprises with presence of networking orientation - Suleman, Areeba (2022)
Family-owned of small and medium enterprises (SMEs) account for a large portion of registered enterprises in the world and contribute significantly to employment and economic growth. Assessing the performance of family-owned SMEs remains a question for researchers and policymakers. The main objective of this study is to evaluate the role of succession planning, entrepreneurial thinking, market orientation, management accounting and networking orientation in assessing the performance of family-owned SMEs. A quantitative approach was used for this study. The theoretical framework of this study was based on recent literature and the resource-based view as the underpinning theory. The study focused on the Pakistan’s sports goods industry, considering the managers/owners as respondents. A questionnaire was used to collect data from the respondents. A sample of 362 questionnaires was used for data analysis. The results revealed that succession planning, entrepreneurial thinking, and market orientation positively and significantly influence the performance of family-owned SMEs. Management accounting shows a positive yet insignificant association with the performance of family-owned SMEs. Furthermore, networking orientation moderates the association between succession planning, entrepreneurial thinking, and family-owned SME performance. However, networking orientation did not moderate the association between market orientation, management accounting and performance of family-owned SMEs. This study indicates a positive yet insignificant association between market orientation, management accounting and performance of family-owned SMEs. The findings of this study significantly contribute to the theory of the resource-based view by examining the relationship between succession planning, entrepreneurial thinking, market orientation, management accounting and the performance of family-owned SMEs in the presence of a moderating role of networking orientation. These findings will facilitate managers/owners, investors, academicians, policymakers, regulators, and the government of Pakistan to understand the significance of latent constructs on the performance of family-owned SMEs